2022
DOI: 10.1021/acs.inorgchem.2c03041
|View full text |Cite
|
Sign up to set email alerts
|

“Dynamical Docking” of Cyclic Dinuclear Au(I) Bis-N-heterocyclic Complexes Facilitates Their Binding to G-Quadruplexes

Abstract: With the aim to improve the design of metal complexes as stabilizers of noncanonical DNA secondary structures, namely, G-quadruplexes (G4s), a series of cyclic dinuclear Au(I) N-heterocyclic carbene complexes based on xanthine and benzimidazole ligands has been synthesized and characterized by various methods, including X-ray diffraction. Fluorescence resonance energy transfer (FRET) and CD DNA melting assays unraveled the compounds' stabilization properties toward G4s of different topologies of physiological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 83 publications
(191 reference statements)
0
6
0
Order By: Relevance
“…[191] In another work, the use of dimeric cyclic analogues of AuTMX 2 did not show stabilization improvements compared to the monomeric benchmark compound, but proved to be beneficial in the case of benzimidazole-based NHCs, although the obtained dimers are less selective than AuTMX 2 . [192]…”
Section: Dna Targetingmentioning
confidence: 99%
See 1 more Smart Citation
“…[191] In another work, the use of dimeric cyclic analogues of AuTMX 2 did not show stabilization improvements compared to the monomeric benchmark compound, but proved to be beneficial in the case of benzimidazole-based NHCs, although the obtained dimers are less selective than AuTMX 2 . [192]…”
Section: Dna Targetingmentioning
confidence: 99%
“…Recent efforts to tune the ligand structure have revealed the importance of an uncrowded xanthine structure for efficient binding to various G4 units, and it has been shown that functionalization of N9 or N1 reduces G4 affinities when compared to the methylated adduct AuTMX 2 [191] . In another work, the use of dimeric cyclic analogues of AuTMX 2 did not show stabilization improvements compared to the monomeric benchmark compound, but proved to be beneficial in the case of benzimidazole‐based NHCs, although the obtained dimers are less selective than AuTMX 2 [192] …”
Section: Gold Complexes As Anticancer Agentsmentioning
confidence: 99%
“…Instead, a number of possibilities were identified in close energetic proximity. As previously observed in the case of other G4 stabilizers, [23,24] the true binding pose can be a combination of orientations that can spontaneously occur due to the low saddle points found between minima, allowing oscillations around a global minimum. Therefore, the overall average GMetaD was calculated at -31.9 ± 4.5 kJ•mol -1 .…”
Section: Dna G4 Stabilizationmentioning
confidence: 59%
“…[17][18][19][20] For instance, gold compounds do not only target proteinsincluding enzymes related to redox homeostasis, DNA repair systems and membrane proteins involved in water/small molecule transport [21,22] but can also act via non-covalent interactions, stabilizing non-canonical DNA secondary structures such as guanine-quadruplexes (G4s). [23,24] The latter are abundant in telomers and in promoter regions of oncogenes, and their stabilization has been proposed as a viable strategy towards anticancer therapy. [25][26][27] Despite these intriguing properties, and although several examples of gold-based metallacages structures have been reported, [28][29][30][31][32][33][34] only a handful of them have been studied to encapsulate small molecules.…”
Section: Introductionmentioning
confidence: 99%
“…The stability of the cobalt(III) Schiff bases, 1 and 2, was investigated via 1 H NMR in a mixture of D 6 -DMSO : D 2 O (80 : 20), following literature described protocols. 38,39 As shown in Fig. S14 and S15, † the spectra of both complexes showed no change over 24 h. As a key step in the compound formation was the oxidation of the metal center to the +3 state, we attempted to expose 1 and 2 to a physiologically relevant concentration of a representative biological reducing agent, the glutathione (GSH) tripeptide, thus assessing the capability of the compounds to revert to their oxidation state.…”
Section: H Nmr Stability Studiesmentioning
confidence: 99%